Computational and experimental studies on the micellar morphology and emission mechanisms of AIE and H-bonding fluorescent composites. Issue 7 (6th February 2023) - Zhou, Guangying; Cheng, Xiaomeng; Yang, Jian; Zhu, Yanyan; Li, Hongping
Abstract : Computational and experimental approaches on the CXL-aided self-assembled morphology and emission mechanisms of AIE and H-bond featured fluorescent composites. Abstract : In this work, we use density functional theory (DFT) calculated competitive hydrogen bonds and dissipative particle dynamics (DPD) simulated micellar structural information to uncover the CO2 -expanded liquid (CXL)-aided self-assembled structure and emission mechanisms of the self-assembled fluorescent composites (SAFCs). Herein, the SAFCs are formed through the self assembly between diblock copolymer polystyrene- b -poly(4-vinylpyridine) (PS- b -P4VP) blend and the dye molecule 4-(9-(2-(4-hydroxyphenyl)ethynyl)-7, 10-diphenylfluoranthen-8-yl)phenol (4 ) in CO2 -expanded toluene at 313.2 K and varied pressures. Firstly, from DPD simulation, we have demonstrated that the addition of CO2 to toluene favors both the expansion of the solvophobic P4VP phase and contraction of solvophilic PS chains, which facilitates the continuous morphological transitions of SAFCs from spherical micelles (3.0 MPa) through wormlike plus spherical micelles (4.0–4.8 MPa) to large vesicles (6.0–6.5 MPa) with pressure rise. Secondly, the DFT calculated bonding energies and IR spectra of the competitive hydrogen bonds help us to clarify the major type of hydrogen bonds determining the fluorescence (FL) performance of the SAFCs. Furthermore, we have revealed the SAFC emission mechanism via the pressure-tunable changes in the aggregation degrees and amount of hydrogen bonds involving 4 and P4VP chains. This work provides a good understanding for the morphology-property control of the self-assembled polymer composites in both microscopic and mesoscopic scales.